Karakteristik Penderita Asma Bronkial Dewasa yang Dirawat Inap di RSUP H. Adam Malik Medan Tahun 2014-2015 - Yuni Alvionita; Rasmaliah .; Mhd Makmur Sinaga (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Bronchial Asthma is one of the chronic disease that attack between 100-150 million people on the world. Based on data from RISKESDAS 2013 asthma prevalence in North Sumatera by 2,4%. The aims of this study characteristics of Bronchial Asthma patients hospitalized in H. Adam Malik General Hospital in 2014-2015. This is descriptive study with case series design. Data analyzed by using Chi-Square, Fisher exact test and Mann-Whitney. Population is all adult Bronchial Asthma patients in 2014-2015 are 91 people and sample is total sampling. The highest proportion of adult Bronchial Asthma patientssufferedin 2014-2015 in the age group 45-54 years based on sex of male of 24,2% and in the age group 45-54 years and 55-64 years old based on female gender of 24,1%, Bataknese (56,0%), housewife (29,7%), senior high school education (41,8%), lives outside of Medan city (64,8%), non-allergen trigger factors (53,8%), Recurrent attacks (86,8%), no family history (63,7%), average length of stay (10 days), not their own source of charge (93,4%), and clinical recovery out patient (89,0%).There is no differences ofage proportionsbased on family history (p=0,119), attacks history (p=1,000), sex based on family history (p=0,359), attacks history (p=0,525),proportions of average length of stay based on age (p=0,258), sex (p=0,480). There is a differences of sex proportions based on trigger factors(p=0,005). It was suggested that hospital complete the patients medical status, including ethnics, employment, education, trigger factors, and family history. Health promotion activities about preventive measures of bronchial asthma should be intensified by health worker. Keywords : Bronchial Asthma, Characteristics, H. Adam Malik General Hospital